2018
DOI: 10.31703/gssr.2018(iii-iv).07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Facilities at Public Schools on Students’ Achievement in Punjab, Pakistan

Abstract: This paper determines the influence of school's physical facilities on students' achievement. The study was quantitative in nature and survey technique was used. The sample of the present study was selected by multi-stage random sampling method from Sahiwal division of Punjab, Pakistan. The researcher developed and validated a Check-List for Physical Facilities (CLPF) prior to data collection. Multiple regression analysis are run in the current research to analyze data. Measurement of the achievement of studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…Abbas (2021) assessed the association between a school having toilet facilities and enrolment at school and discovered that a school with a toilet facility has a higher enrolment rate and according to the gender breakdown of the results, having a toilet facility was associated with a higher enrolment in girls-only schools. A similar study by Arshad et al (2018) revealed that all the physical facilities contributed about 15.4% towards students' academic achievement. Tisia (2012) conducted a study to establish the institutional factors influencing girl-child education in public primary schools in Tenges division, Baringo district, Kenya and findings revealed that lack of water and good toilets influenced girl-child participation in education.…”
Section: Relationship Between School Physical Facilities and The Qual...mentioning
confidence: 76%
See 1 more Smart Citation
“…Abbas (2021) assessed the association between a school having toilet facilities and enrolment at school and discovered that a school with a toilet facility has a higher enrolment rate and according to the gender breakdown of the results, having a toilet facility was associated with a higher enrolment in girls-only schools. A similar study by Arshad et al (2018) revealed that all the physical facilities contributed about 15.4% towards students' academic achievement. Tisia (2012) conducted a study to establish the institutional factors influencing girl-child education in public primary schools in Tenges division, Baringo district, Kenya and findings revealed that lack of water and good toilets influenced girl-child participation in education.…”
Section: Relationship Between School Physical Facilities and The Qual...mentioning
confidence: 76%
“…It is advised that the government and society enhance school infrastructure for girls and modify attitudes about girls' education in order to improve girls' academic achievement. Arshad, Qamar, and Gulzar (2018) investigated the impact of physical school facilities on student achievement.…”
Section: School Physical Facilities and The Quality Of Girls' Educationmentioning
confidence: 99%
“…In the Pakistani context, various approaches have been deployed to improve and measure students' mathematics achievements; total quality management (Mahmood & Ismail, 2018), metacognition (Habib & Rana, 2020), the effect of ICT (Ishaq et al, 2020;Khan, 2020), the influence of physical facilities (Arshad et al, 2018), executive functioning (Hania et al, 2019), parental influence (Ahmed et al, 2019), the effect of cooperative learning (Atiq et al, 2021) and problemsolving (Ahmad et al, 2022). Even then, students' mathematics results are still unsatisfactory (Mughal et al, 2021;Ullah et al, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…School support facilities like tablet, I.T Lab, ventilation, first aid medical box, gas, store room, ECE/kids room, staff room and library contributed about 15.8% towards academic achievement at Punjab Education Foundation partner schools significantly (Arshad, Ahmed & Tayyab, 2019). Arshad, Qamar & Gulzar (2018) showed that physical facilities put 15.4% influences on academic achievement (Odigwe & Eluwa, 2013). Farooqi, et al (2015) compared quantitatively the provision of physical facilities at government and private secondary schools in Punjab.…”
Section: Review Of Related Literaturementioning
confidence: 99%